2021
DOI: 10.1038/s41392-021-00740-y
|View full text |Cite
|
Sign up to set email alerts
|

ACE2-targeting monoclonal antibody as potent and broad-spectrum coronavirus blocker

Abstract: The evolution of coronaviruses, such as SARS-CoV-2, makes broad-spectrum coronavirus preventional or therapeutical strategies highly sought after. Here we report a human angiotensin-converting enzyme 2 (ACE2)-targeting monoclonal antibody, 3E8, blocked the S1-subunits and pseudo-typed virus constructs from multiple coronaviruses including SARS-CoV-2, SARS-CoV-2 mutant variants (SARS-CoV-2-D614G, B.1.1.7, B.1.351, B.1.617.1, and P.1), SARS-CoV and HCoV-NL63, without markedly affecting the physiological activiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…Together with our previous study, 5 our data suggest that 3E8 is potentially a potent and “broad-spectrum” blocker of multiple coronaviruses that utilize ACE2 as entry receptors, including SARS-CoV-2 Delta, Omicron, Alpha, Beta, Kappa, Gamma, SARS-CoV, and HCoV-NL63.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Together with our previous study, 5 our data suggest that 3E8 is potentially a potent and “broad-spectrum” blocker of multiple coronaviruses that utilize ACE2 as entry receptors, including SARS-CoV-2 Delta, Omicron, Alpha, Beta, Kappa, Gamma, SARS-CoV, and HCoV-NL63.…”
supporting
confidence: 84%
“…3E8 also blocked the live SARS-CoV-2 infection of Vero E6 cells and in a prophylactic mouse model of COVID-19. 5 In this study, we showed that 3E8 could potentially block Delta and Omicron VOCs, demonstrating further that it was a potent and “broad-spectrum” blocker of all coronaviruses that utilize hACE2 as entry receptors.…”
mentioning
confidence: 60%
“…As a negative control, we also transfected VEEV-eGFP replicon RNA into naïve BHK-21 cells or BHK-21 cells pre-transfected with hACE2 expression plasmid, and only scattered GFP positive cells were detected at each time point post transfection ( Figure 4 (A), lower panel; Figure 4 (B)). For the antibody inhibition method, a neutralizing antibody against hACE2, 3E8 [ 35 ] was incubated with VEEV-SARS-CoV-2-S-eGFP replicating cells for 18 h. As shown in Figure 4 (C,D), the addition of 3E8 greatly reduced syncytium formation compared with the antibody-absent control. Collectively, these results provide strong evidence that VEEV-SARS-CoV-2-S-eGFP induced syncytium formation can mimic what the authentic SARS-CoV-2 does in a S- and receptor-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid residues from W436 to Q506 inside RBD shape the Receptor Binding Motif (RBM), which carries 11 contact positions with ACE2 (5). The RBD region has received great attention, as it seems to be a major target of antibodies against the virus and other therapeutic interventions (6)(7)(8). In the RBD region, Omicron variant carries 15 mutations, 10 of which are identified in the RBM area (Fig.…”
Section: Omicron-specific C/h-crups That Belong To the Receptor Binding Domainmentioning
confidence: 99%